(untitled) (The International Journal for Scientific Research, 2025)
The current research dealt with (the conceptual dimensions of conflict scenes and their representations in Sumerian art), through studying the religious, political, environmental, ideological and social dimensions from which the conflict scene emerged, which was represented in the aesthetic structure of cylindrical seals, obelisks, stone tablets and statues, during the Sumerian era. Therefore, the researcher sought in the first chapter to clarify the problem of the research, its importance and the need for it, in addition to the aim of the research, which was represented by the following: "Identifying the conceptual dimensions of conflict scenes and their representations in Sumerian art." Then the researchers concluded the aforementioned chapter by defining the terms that are directly related to the title of the research and its objectives. As for the second chapter, it included a presentation of the theoretical framework and previous studies, and it consisted of two sections. The first section established the conflict conceptually. The second section dealt with the conflict: an approach in ancient Sumerian art. The third chapter was devoted to monitoring the research community and the tool that included collecting information, so samples were adopted from it in an intentional manner, and they amounted to (3) sculptural works that covered the limits of the research by adopting the descriptive analytical method for the purpose of analyzing them according to the axes of the analysis tool that the researcher adopted. As for the fourth chapter, it included the results of the research, which included: · The scenes of the conflict were evident in the ability of the Sumerian artist to adopt the realistic style in embodying human bodies with political dimensions that escalated their desired essential connotations, and religious thought is one of the most important pressing dominants in the structure of Sumerian art, and this is what appeared in all samples. · The Sumerian embodied and prominent art expressed the artistic feelings formed in the thought of the Sumerian artist through the diversity of topics, which carry religious and political dimensions that represent the social structure of the Sumerians. Then the conclusions that emerged from it the possibility of achieving the research objectives through the tool designed by the researcher, including: · Sumerian art in its various forms embodied religious thought and political dimension, by referring them to pictorial systems with aesthetic value full of symbolism directed towards the absolute and invisible powers. · The intellectual contemplations of the Sumerian sculptor contributed to the diversity of conflict scenes at the level of (sculptural or bas-relief), and the technical and directing treatments varied, as an attempt to depict and represent these intellectual contemplations and refer them to a symbolic meaning that has a tangible material existence. I also made an effort to mention a number of recommendations and suggestions followed by sources and appendices.